A case of contact stomatitis of the oral floor caused by magnesium oxide in an elderly with paralysis. Issue 2 (14th July 2022) - Okubo, Masahiko; Kamimura, Hideyuki; Fukushima, Yosuke; Ito, Ko; Sato, Tsuyoshi; Kokabu, Shoichiro
Abstract: Background: On the mucosa, the retention of drugs including magnesium oxide for laxative sometimes causes drug‐induced contact mucositis. Case presentation: A 72‐year‐old man presented with discomfort in the oral floor. He suffered from paralysis on the right side of his body. After his meal, it was observed magnesium oxide were retained on the right side of the oral floor. After our instruction of taking drugs with food thickening agents, his mucosa became normal soon. Conclusion: We realized that the supervising of taking medicine in the right way is important for the patients such as oral dysphagia especially with elderly and paralysis.